Outcomes of Anterior Decompression and Anterior Instrumentation in Thoracolumbar Burst Fractures—A Prospective Observational Study With Mid-Term Follow-up. Issue 4 (April 2022) - Mittal, Samarth; Rana, Arvind; Ahuja, Kaustubh; Ifthekar, Syed; Yadav, Gagandeep; Sudhakar, Pudipeddi Venkata; Sinha, Shivendra K.; Kar, Santanu; Sarkar, Bhaskar; Kandwal, Pankaj; Farooque, Kamran
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: To analyze the functional, neurological, and radiological outcomes after anterior surgery in thoracolumbar burst fractures. Design: Prospective observational study. Setting: Tertiary care hospital. Patients: Thirty-six patients with thoracolumbar burst fractures (T11-L2). Intervention: Anterior decompression, anterior column reconstruction with mesh cage, and instrumented stabilization. Outcome: Functional (Visual Analog Score, Oswestry Disability Index, and Spinal Cord Independence Measure), neurological (ASIA Impairment Scale), and radiological (kyphosis, anterior vertebral height loss, canal encroachment %) parameters. Results: Patients were prospectively followed for a mean duration of 5.9 ± 3.2 years (2.4–10 years). Statistically significant improvement was noted in functional outcomes from preop values ( P -value < 0.001). 29 patients (80.5%) had improvement in neurology after surgery at the final follow-up with a positive correlation with % change in canal encroachment (r = 0.64, P −0.018). The mean preoperative kyphosis of 29.1 ± 11.9 degrees got corrected to 9.4 ± 3.8 degrees in immediate postop and 15.7 ± 11.8 at the final follow-up( P < 0.001). Preoperative mean canal encroachment of 58.5 ± 15.7% was reduced to 6.5 ± 3.2% postoperatively ( P < 0.001). Two patients developed neurological complications (subacute progressive ascending myelopathy), and 5 patients developed pulmonary complications. No pseudarthrosis, implant loosening, or cage migration was noted in any patient. Conclusion: Anterior surgery performed in 36 patients with thoracolumbar burst fractures in our study showed good outcomes. 80.5% of patients improved in neurology after surgery by at least one ASIA Impairment Scale grade. There was statistically significant improvement noted in radiological outcome (Kyphosis and Canal encroachment %) and functional outcome (Visual Analog Score, Oswestry Disability Index, and Spinal Cord Independence Measure score) after surgery in immediate postop and at the final follow-up. Only 13.8% of patients developed pulmonary complications that were managed successfully with chest drain. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.